2012
DOI: 10.1120/jacmp.v13i6.4019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of field size on stopping‐power ratios in‐ and out‐of‐field: quantitative data for the BrainLAB m3 micro‐multileaf collimator

Abstract: The objective of this work is to quantify the systematic errors introduced by the common assumption of invariant secondary electron spectra with changing field sizes, as relevant to stereotactic radiotherapy and other treatment modes incorporating small beam segments delivered with a linac‐based stereotactic unit. The EGSnrc/BEAMnrc Monte Carlo radiation transport code was used to construct a dosimetrically‐matched model of a Varian 600C linear accelerator with mounted BrainLAB micro‐multileaf collimator. Stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A critical point is the energy dependence of the detector response. The difference in energy spectra 27,28 should be considered in any out-of-field dose measurements relative to in-field dose levels. Studies on the stopping power ratio, between water and air, showed that 28 the variation in the out-of-field region relative to the in-field for a 6 MV beam is of more than 1% (for a 10 × 10 cm 2 field).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A critical point is the energy dependence of the detector response. The difference in energy spectra 27,28 should be considered in any out-of-field dose measurements relative to in-field dose levels. Studies on the stopping power ratio, between water and air, showed that 28 the variation in the out-of-field region relative to the in-field for a 6 MV beam is of more than 1% (for a 10 × 10 cm 2 field).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in energy spectra 27,28 should be considered in any out-of-field dose measurements relative to in-field dose levels. Studies on the stopping power ratio, between water and air, showed that 28 the variation in the out-of-field region relative to the in-field for a 6 MV beam is of more than 1% (for a 10 × 10 cm 2 field). Moreover, when measuring the dose in a point where the energy spectrum is continuously varying (from in-field to out-of-field during the same irradiation), as in intensity modulation, it is almost impossible, to correctly compensate the measurements for the different energy response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In megavoltage radiation beams, the spectrum can also change significantly enough to affect dose measurement, for example in the beam penumbra or in small fields (Taylor et al 2012).…”
Section: Measurements and Calculations: The Role Of Monte Carlo Simul...mentioning
confidence: 99%